2010
DOI: 10.1080/13557851003615545
|View full text |Cite
|
Sign up to set email alerts
|

Internalization symptoms, perceived discrimination, and ethnic identity in indigenous Sami and non-Sami youth in Arctic Norway

Abstract: Culture-specific protective factors were discussed as potential explanations for the similarities between Sami and non-Sami youth. The present study documented a relationship between internalization symptoms and ethnic identity, perceived discrimination, and language loss. These findings could be understood as consequences of the recent colonial history and oppression of the indigenous Sami.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
51
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 54 publications
9
51
0
4
Order By: Relevance
“…Differences between indigenous and non-indigenous groups were most evident and uniform in suicide studies, where the rates were around two to ten times higher among indigenous youth (Lehti et al, 2009). In Norway only few difference between Sami and non-Sami populations were found in studies on suicidal behaviour, emotional problems and alcohol use (Bals, Turi, Skre, & Kvernmo, 2010;Eriksen, 2017;Lehti et al, 2009). Bals et al (2010) point out that this lack of difference often can be "attributed to the good living conditions and positive socio-cultural development in Sami areas".…”
Section: Mixed Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Differences between indigenous and non-indigenous groups were most evident and uniform in suicide studies, where the rates were around two to ten times higher among indigenous youth (Lehti et al, 2009). In Norway only few difference between Sami and non-Sami populations were found in studies on suicidal behaviour, emotional problems and alcohol use (Bals, Turi, Skre, & Kvernmo, 2010;Eriksen, 2017;Lehti et al, 2009). Bals et al (2010) point out that this lack of difference often can be "attributed to the good living conditions and positive socio-cultural development in Sami areas".…”
Section: Mixed Methodsmentioning
confidence: 99%
“…In Norway only few difference between Sami and non-Sami populations were found in studies on suicidal behaviour, emotional problems and alcohol use (Bals, Turi, Skre, & Kvernmo, 2010;Eriksen, 2017;Lehti et al, 2009). Bals et al (2010) point out that this lack of difference often can be "attributed to the good living conditions and positive socio-cultural development in Sami areas". However, in the NAAHS study (2003)(2004)(2005) Sami youth reported more suicide attempts last year, as well as more concurrent adversities than non-Sami peers (Reigstad & Kvernmo, 2017).…”
Section: Mixed Methodsmentioning
confidence: 99%
See 3 more Smart Citations